2005
DOI: 10.1002/jclp.20235
|View full text |Cite
|
Sign up to set email alerts
|

The influence of outcome measures in assessing client change and treatment decisions

Abstract: This study investigated the influence that information in the form of outcome measures and client verbal reports can have on treatment decisions and clinician judgment of client change. A random national sample of psychologists (N=810, 45% response rate) were given clinical vignettes and asked questions regarding their view of client progress and subsequent treatment decisions. Despite clinicians reporting that verbal report is more influential in their actual clinical practice than outcome measure information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
0
25
2
Order By: Relevance
“…This is not necessarily the same as what therapists state they would do in this circumstance (Hatfi eld & Ogles, 2006). Future research will need to investigate if therapists actually engage in the therapeutic strategies they espouse.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is not necessarily the same as what therapists state they would do in this circumstance (Hatfi eld & Ogles, 2006). Future research will need to investigate if therapists actually engage in the therapeutic strategies they espouse.…”
Section: Introductionmentioning
confidence: 84%
“…One possible explanation is that therapists are often not detecting their clients' deterioration when it is occurring (Hatfi eld & Ogles, 2006). Again, if therapists are unable to detect client deterioration, they will not have reason to make appropriate treatment decisions in response to the deterioration.…”
Section: Introductionmentioning
confidence: 95%
“…In a 3 X 3 research design, a larger sample size would have been preferable, as there was a low number of participants in many of the cells. The Hatfield and Ogles (2006) study rephcated here had over twice that sample size. Further, Spengler et al (2009) suggest diat, consistent with their findings of a small effect size, studies examining clinical judgment and clinical experience "will tend to have low power, and a majority will likely report stadsdcally nonsignificant [results]" (p. 381).…”
Section: Limitationsmentioning
confidence: 97%
“…The materials used for this investigation were a revised version of the survey used in a previous study by Hatfield and Ogles (2006). Permission was granted to modify (D. Hatfield, personal communication.…”
Section: Instrumentsmentioning
confidence: 99%
“…Hatfield and Ogles (2006) found that outcome measures might be instrumental in leading therapists to alter treatment in situations of potential treatment failure. The benefits of standardized outcome assessment warrant greater attention because of the potential for improved therapeutic services provided by practitioners (Barkham et al, 2001;Kordy, Hannö ver, & Richard, 2001;Lambert et al, 2001Lambert et al, , 2002Lueger et al, 2001;Whipple et al, 2003).…”
Section: Introductionmentioning
confidence: 97%